2014
DOI: 10.1007/s00221-014-3902-4
|View full text |Cite
|
Sign up to set email alerts
|

Affective motivational direction drives asymmetric frontal hemisphere activation

Abstract: Decades of research have shown that the left- and right-frontal cortical regions are asymmetrically involved in affective processing. Specifically, this past work has demonstrated that greater left-frontal activation is related to positive-approach, and greater right-frontal activation is related to negative-withdrawal. However, much of this past work confounded motivation and affective valence. The current experiment sought to illuminate whether frontal asymmetry is related to motivation or affective valence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 67 publications
5
51
1
Order By: Relevance
“…This finding is in line with the capability model (see Coan et al, ). It extends previous research on LPP modulation (Gable & Harmon‐Jones, ; Gable & Poole, ; Poole & Gable, ) and shows that subjective ratings of both valence and arousal can also be influenced by state asymmetrical frontal brain activation. This association between emotion‐specific enhanced negative evaluations with larger state right frontal asymmetry is in line with the specific predictions of the approach withdrawal model (i.e., larger withdrawal motivation toward negative stimuli).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This finding is in line with the capability model (see Coan et al, ). It extends previous research on LPP modulation (Gable & Harmon‐Jones, ; Gable & Poole, ; Poole & Gable, ) and shows that subjective ratings of both valence and arousal can also be influenced by state asymmetrical frontal brain activation. This association between emotion‐specific enhanced negative evaluations with larger state right frontal asymmetry is in line with the specific predictions of the approach withdrawal model (i.e., larger withdrawal motivation toward negative stimuli).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous studies (Gable & Harmon‐Jones, ; Harmon‐Jones, , Harmon‐Jones et al, ), state frontal asymmetry within the 6 s of picture viewing did not differ between picture types (for all comparisons p > .80). However, based on previous findings (e.g., Poole & Gable, ), we examined the hypothesis that individuals' differences in state frontal asymmetry were related to emotional responses for pictures similar in emotional valence. Results revealed that larger right frontal activation while viewing negative pictures was related to more negative subjective valence, r = .393, p = .024, R 2 = .154, and higher arousal ratings, r = −.480, p = .005, R 2 = .230, toward these pictures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations